2021
DOI: 10.1101/2021.07.14.452003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNase HI depletion strongly potentiates cell killing by rifampicin in mycobacteria

Abstract: Multidrug resistant (MDR) tuberculosis (TB) is defined by the resistance of Mycobacterium tuberculosis, the causative organism, to the first-line antibiotics rifampicin and isoniazid. Mitigating or reversing resistance to these drugs offers a means of preserving and extending their use in TB treatment. R-loops are RNA/DNA hybrids that are formed in the genome during transcription, and can be lethal to the cell if not resolved. RNase HI is an enzyme that removes R-loops, and this activity is essential in M. tub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 82 publications
(59 reference statements)
2
2
0
Order By: Relevance
“…ΔrnhC sensitivity was detected in two independent rnhC in-frame mutants (Figure S3C) and ectopic expression of rnhC in the ΔrnhC mutant restored the WT sensitivity (Figures 4C and S3D) indicating that RnhC confers rifampicin tolerance. This finding confirms recently published results using an M. smegmatis rnhC mutant that was hypersensitive to Rifampin using an MIC based assay (35).…”
Section: Deletion Of Rnhc Confers Sensitivity To Rifampicinsupporting
confidence: 93%
See 3 more Smart Citations
“…ΔrnhC sensitivity was detected in two independent rnhC in-frame mutants (Figure S3C) and ectopic expression of rnhC in the ΔrnhC mutant restored the WT sensitivity (Figures 4C and S3D) indicating that RnhC confers rifampicin tolerance. This finding confirms recently published results using an M. smegmatis rnhC mutant that was hypersensitive to Rifampin using an MIC based assay (35).…”
Section: Deletion Of Rnhc Confers Sensitivity To Rifampicinsupporting
confidence: 93%
“…The RNase HI enzyme encoded by rnhC, while coessential with RnhA, also contains an autonomous C terminal acid phosphatase domain that does not contribute to its essential function (21,22). Al-Zubaidi et al recently demonstrated that the rnhC mutant of M. smegmatis led to the accumulation of R-loops and a sensitivity to rifampicin (35), a finding (rif sensitivity) we replicate in this study. However, our data indicates that the RNase HI activity of the RnhC protein is not required for the rifampicin resistance phenotype and that the acid phosphatase activity is the important biochemical activity.…”
Section: Rnhc Protects Against Rifampicin Through Its Acid Phosphatas...supporting
confidence: 84%
See 2 more Smart Citations